Public perception of fish massage impact at the ‘Tagal’ areas in Sabah - Chan, Kaede Lip Chung; Andy Russel Mojiol (e-VIBS, Faculty of Science and Natural Resources, 2020)
The “Tagal system” is a traditional water conservation that prohibits fishing activities in the river for a predetermined time. The initiation of this system is to sustain the inland river resources, restoration of polluted river and generate income for the inhabitants. Furthermore, the „Tagal‟ system is evolved into ecotourism activities such as fish massage which is beneficial to the inhabitants. However, the hygiene and management of fish massage becomes an issue for the users. Surveys were conducted at two Tagal areas namely „Tagal‟ Luanti Moroli River, Ranau, and „Tagal‟ Kiulu, Tamparuli. Result from the surveys have shown that the majority agreed fish massages are beneficial activities and would be safe to be conducted at „Tagal‟ area. The majority also agreed to participate in the „Tagal‟ conservation because it promotes good sustainable management for the inland river. Moreover, Willingness to Pay (WTP) would be a good management practice for the inhabitants but the linear regression model shows that only marital status, level of education, occupation, and distance variables were correlated with WTP. Further investigation is necessary in this field of study in the future.